2004
DOI: 10.1016/j.jnoncrysol.2004.02.016
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of the growth dynamics of amorphous and microcrystalline silicon

Abstract: The qualitative description of the major microstructure characteristics of microcrystalline silicon is achieved through a threedimensional discrete dynamical growth model. The model is based on three fundamental processes that determine surface morphology: (1) random deposition of particles, (2) local relaxation and (3) desorption. In this model, the incoming particle reaching the growing surface takes on a state variable representing a particular way of being incorporated into the material. The state variable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 9 publications
(12 reference statements)
1
9
0
Order By: Relevance
“…All these results indicate the manifestation of phase transition from amorphous to polycrystalline structure with increasing ZnO film thickness. Studies on similar thickness dependent crystallinity of various materials have also been reported by researchers [13][14][15]. In the initial stage of the film growth, only very few and small nanocrystallitic islands may exist in the film (thus should be considered as amorphous film).…”
Section: Introductionsupporting
confidence: 54%
“…All these results indicate the manifestation of phase transition from amorphous to polycrystalline structure with increasing ZnO film thickness. Studies on similar thickness dependent crystallinity of various materials have also been reported by researchers [13][14][15]. In the initial stage of the film growth, only very few and small nanocrystallitic islands may exist in the film (thus should be considered as amorphous film).…”
Section: Introductionsupporting
confidence: 54%
“…Note that the number of states n used for representing the different crystallographic orientations must be at any rate higher than 10 according to crystallographic considerations exposed in [6]. The first condition is fulfilled with all points of the phase diagram except the two regions defined by n<5 and t<4 for which the crystalline fraction is high even without any etching.…”
Section: Resultsmentioning
confidence: 99%
“…Details are given in [6]; the main simulation steps are summarized here. Random deposition and relaxation: A cubic particle is released from a position randomly chosen above the layer surface.…”
Section: Model Descriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…The texture of the back reflector in superstrate technology is mainly influenced by two factors: the front contact texture and the evolution of the growing absorber layer's surface. This modification is governed by a flattening of the rough interface and by the growth inherent texture of the absorber layers [21,[58][59][60]. Studies have shown that the growth of silicon is non-conformal [21,58,61].…”
Section: Solar Cells On Single Textured Zno:al With Different Featurementioning
confidence: 99%